IMPLEMENTASI BACA, GAMBAR, CERITA SEBAGAI UPAYA PENINGKATAN LITERASI LITERASI SISWA KELAS III SDN 1 SANDIK - Nurannisa Ramadhani; Siti Hawa; Herly Yuniarti; Rismi; Aurelia Salsabila; Alfina Dwijayanti; Syafruddin Muhdar (STKIP Subang, 2026)
The low interest in reading and the difficulty in understanding texts among elementary school students remain serious challenges that affect overall learning success. This study aims to describe and analyze the implementation of the Read, Draw, Tell